A case of encapsulated papillary carcinoma of the breast treated with emergency surgery due to sudden hemorrhage. (2019) - Yoneyama, Kimiyasu; Nakagawa, Motohito; Hara, Asuka
Abstract: Introduction: Emergency surgery is rare in management of breast cancer. We report a case of encapsulated papillary carcinoma (EPC) of the breast where emergency surgery was performed because of unsuccessful control of hemorrhage. Presentation of case: A 62-year-old woman visited our hospital complaining of sudden bleeding from the right breast. She had been aware of the tumor for a year, but had left it unattended. It had been increasing in size rapidly for a few days before presentation. Computed tomography showed a hypervascular cystic tumor 9 cm in diameter. Bleeding was observed from a skin breach in the right breast, from which a clot was removed and the wound compressed with gauze. We attempted unsuccessfully to control the hemorrhage over the next 3 days, but the patient became anemic, so emergency surgery was performed to control the bleeding. Histopathology revealed the tumor as estrogen receptor- and progesterone receptor-positive EPC, with a human epidermal growth factor receptor 2 score of 0. Discussion: There have been only 5 reports of breast cancer treated with emergency surgery. EPC was previously considered an in situ lesion, but the lack of a myoepithelial layer at the lesion's periphery may represent a low grade or indolent form of invasive carcinoma and prognosis is usually good. However, if bleeding into the cyst occurs and hemostasis is difficult, emergency surgery should be considered. Conclusion: Emergency surgery is rare in breast cancer but should always be considered as an option when hemorrhage is not readily controlled.